Successions of rare and abundant microbial subcommunities during fish carcass decomposition in a microcosm under the influence of variable factors. Issue 1 (26th March 2022) - Hilal, Mian G; Zhou, Rui; Yu, Qiaoling; Wang, Yijie; Feng, Tianshu; Li, Xiangkai; Li, Huan
Abstract: Animal carcasses are hotspots of ecological activity. The study of the role of microbes in carcass decomposition has been exclusively focused on microbes with higher abundance. The comparative study of abundant and rare subcommunities associated with decomposition needs in-depth exploration. The current experiment has been conducted on the decomposition of a fish carcass in a microcosm. We conducted 16S rRNA gene sequencing of the microbial communities. The correlation of the physicochemical properties of tap and Yellow river water with the microbial communities was evaluated. Proteobacteria, Bacteroidetes, Firmicutes, and Actinobacteria were found to be the dominant phyla in both abundant and rare subcommunities. Among bacteria, the Acidobacteria, Planctomycetes, and Cyanobacteria were found only in the rare subcommunity. In both subcommunities, the abundance of Proteobacteria was found to increase over time, and that of Firmicutes to decrease. The rare subcommunity shows higher alpha diversity than the abundant one. The variation in the abundant subcommunity was influenced by time and water type, and that in the rare subcommunity was influenced by pH and water type. These results have implications for future research on the ecological role of rare and abundant subcommunities in the decomposition of carcasses in the aquatic ecosystem.